The effects of the toxic dinoflagellate Alexandrium on feeding, reproduction and mortality of the copepod Acartia: A systematic review employing weighted linear models - Felpeto, Aldo Barreiro; Frangopulos Rivera, Maximo Jorge; Vasconcelos, Vitor Manuel (My University, 2024)
The study of interactions between copepods of the genus Acartia and toxic dinoflagellates of the genus Alexandrium has been an important topic during the last four decades. Feeding behavior and physiological responses of copepods have been studied in laboratory and field experiments, sometimes with contradictory results. More recently, an evolutionary adaptive mechanism leading to enhanced tolerance of Alexandrium toxins in a population of Acartia experiencing chronic exposure to these dinoflagellates has been reported. In the present work, we collected data from the existing studies on the effects of Alexandrium on feeding, reproduction and mortality of Acartia. With these data, we performed a systematic review consisting of a secondary analysis employing general or generalized linear models, weighting data from different studies by the reciprocal of their standard deviation. Our first aim was to overcome shortcomings of individual studies: limited ranges of the variables and overlooked variables (experiment length, population adaptation). These shortcomings could have led to inconsistent conclusions by missing heterogeneous patterns in copepod responses and in the interactions between variables. Our second aim was to test the enhanced physiological performance of chronically exposed relative to naïve copepod populations over a wide geographic range. We found that the feeding rate is enhanced by increased food biomass, irrespective of the food type. Toxins do not have a clear effect on egg production and have a bi-phasic effect on egg hatching success, which was negative above a specific threshold. Toxins also increased mortality. Experiment length had a positive effect on egg production and negative on egg hatching. Naïve copepod populations showed consistently lower ingestion of Alexandrium and egg hatching rates, thereby supporting the spread of the aforementioned mechanism across populations over a wide geographic range.
Keywords: alexandrium; acartia; systematic review; pst; adaptation